Model of a conveyor-type transport system with stochastic input material flow - Pihnastyi, Oleh; Sobol, Maksym; Burduk, Anna (CEUR Workshop Proceedings, 2025)
Belt conveyor systems play a key role in ensuring the continuous transportation of bulk materials in mining enterprises, both in open and underground conditions. One of the urgent tasks is to increase energy efficiency and material loading factor, which allows to reduce operating costs and meet modern environmental requirements. In this paper, the behavior of the transport system with a stochastic nature of the input material flow is investigated. A mathematical model describing the movement of material along the conveyor route is developed, taking into account the statistical characteristics of the input flow, modeled as a stationary random process. A review of modern approaches to transport system control is given, including belt speed regulation, flow control from accumulation bins, and the use of reversible conveyors for route optimization. Particular attention is paid to the influence of the randomness of the input flow on the system performance parameters. The obtained results allow us to identify dependencies between the stochastic characteristics of the input flow and key parameters of the system, which contributes to the development of more efficient and adaptive conveyor transport control strategies.
Keywords: belt conveyor; input material flow; stochastic material flow; normal distribution; stochastic process realization; statistical characteristic; correlation function; ergodic process